PENGARUH PEMAHAMAN PERISTIWA G30S PKI DAN DISIPLIN BELAJAR PENDIDIKAN PANCASILA TERHADAP SIKAP NASIONALISME PESERTA DIDIK DI SMA COLOMADU - Febriyanti, Elisa; Bambang Setyadi, Yulianto (Universitas Muhammadiyah Surakarta, 2025)
This study aims to examine the influence of understanding the G30S PKI incident on students' nationalist attitudes at SMA Negeri Colomadu, to analyze the influence of discipline in learning Pancasila Education on students' nationalist attitudes, and to investigate the combined influence of understanding the G30S PKI incident and discipline in learning Pancasila Education on students' nationalist attitudes at SMA Negeri Colomadu. The research approach used is quantitative correlational with multiple linear regression analysis techniques. The population of this study consists of all students at SMA Negeri Colomadu in the 2024/2025 academic year, totaling 956 students from grades X, XI, and XII. The sampling technique used was proportional random sampling, selecting 10% of the total population, resulting in a sample size of 96 students. Primary data were collected through questionnaires developed based on the indicators of each variable and had passed validity and reliability testing. The results of the study indicate that: (1) there is a positive and significant influence between the understanding of the G30S PKI incident and nationalist attitudes, with the calculated t-value greater than the t-table value (4.015 > 1.661) and a significance level of 0.000 < 0.05, (2) there is a positive and significant influence between discipline in learning Pancasila Education and nationalist attitudes, with the calculated t-value greater than the t-table value (4.401 > 1.661) and a significance level of 0.000 < 0.05, and (3) there is a joint influence of understanding the G30S PKI incident and discipline in learning Pancasila Education on students’ nationalist attitudes, with a calculated t-value greater than the t-table value (4.401 > 1.661) and a significance level of 0.000 < 0.05. This study provides an important call to strengthen technology-based learning and the internalization of Pancasila values in the learning process to enhance students' character and sense of national identity.